Innovation of Natural Therapy in Continuity of Care (CoC) Midwifery - Dwi Cipto Astuti; Syarifah; Fitria Hikmatul Ulya (Karya Kesehatan Siwalima, 2026)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are key indicators of a nation's health status. Elevated rates are often associated with unmonitored complications during pregnancy and childbirth. The Continuity of Care (CoC) approach provides a continuous care model that enables early detection of potential complications through sustained relationships between midwives and patients. This study aims to provide comprehensive midwifery care to Mrs. Y (41 years old) and Mrs. D (22 years old), encompassing the third trimester of pregnancy, labor, newborn care, postpartum care, and family planning services. The research employed a descriptive observational design using Varney’s seven-step midwifery management approach and SOAP documentation. The results showed that both patients experienced physiological pregnancies. The labor process was normal, with care focusing on pain management for Mrs. Y and comprehensive management of stages I–IV of labor for Mrs. D. The newborns were healthy, supported by the implementation of Early Initiation of Breastfeeding (EIB). The postpartum period progressed without complications, facilitated by education on nutrition and breastfeeding techniques. At the end of the care period, both patients chose long-term contraceptive methods, with Mrs. Y opting for tubectomy (MOW). In conclusion, the implementation of CoC effectively supports a safe reproductive process and minimizes the risk of complications through continuous monitoring and patient education.